Perencanaan Dan Pelaksanaan Pembelajaran Pendidikan Agama Islam Di Madrasah Aliyah Raudlatul Ulum Putri - Busthomi, Yazidul; A’dlom, Syamsul (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2019)
Madrasah Aliyah Raudlatul Ulum Putri in the village of Ganjaran Gondanglegi Malang including formal education institutions. The atmosphere in the Madrasah is family-based, based on compassion and mutual respect. However, the fact that is related to the learning of Islamic religious education in Madrasahs is quite astonishing. Learning about Islamic religious education in Madrasahs is impressive. So the authors are interested in conducting research by raising a title for planning and implementing learning of Islamic religious education in Madrasah Aliyah Raudlatul Ulum Putri, Ganjaran Gondanglegi village, Malang. The results of the study show that the planning and implementation of learning Islamic religious education at the Madrasah Aliyah Raudlatul Ulum Putri are as follows: 1. Planning the learning of Islamic religious education in the Aliyah Raudlatul Ulum Putri Madrasah as follows: a. The teacher makes learning devices, b. The teacher sets learning goals, c. The teacher selects and develops teaching materials, d. The teacher chooses the appropriate teaching media, e. The teacher chooses and utilizes learning resources. 2. The implementation of learning Islamic education in the Aliyah Raudlatul Ulum Putri Madrasah is as follows: a. The teacher creates the right learning climate / atmosphere, b. The teacher observes learning activities, c. The teacher organizes students in learning activities, d. The teacher chooses and sets the learning method that is considered the most appropriate and effective, e. The teacher evaluates the learning achievement of students, f. The teacher carries out follow-up of the assessment results.